ATRX Mutations in Pineal Parenchymal Tumors of Intermediate Differentiation. Issue 8 (27th May 2019) - Martínez, Haydee; Nagurney, Michelle; Wang, Zi-Xuan; Eberhart, Charles G; Heaphy, Christopher M; Curtis, Mark T; Rodriguez, Fausto J
Abstract: Pineal parenchymal tumors are rare neoplasms, ranging from WHO Grade I to IV. There are few studies characterizing the molecular profiles of these tumors. ATRX alterations are strongly associated with the presence of the alternative lengthening of telomeres (ALT) phenotype, and within the central nervous system they tend to occur in subsets of gliomas, including those with IDH, NF1, or histone (H3 K27M or G34) mutations. Here, we identified ATRX frameshift mutations by next generation sequencing associated with corresponding protein loss in 2 cases of pineal parenchymal tumors of intermediate differentiation (PPTID) developing in a 21-year-old woman and a 64-year-old man. In contrast, we identified partial ATRX loss in 1 pineoblastoma, among 14 pineal parenchymal tumors of various grades (6 pineoblastomas, 4 pineocytomas, and 4 PPTID) using tissue microarrays; ALT was absent in these cases. Evaluating the cBioPortal database, an ATRX mutation was identified in one (of 3 total) PPTIDs analyzed. Thus, ATRX mutations associated with protein loss and ALT develop in a small subset of pineal parenchymal tumors and may be limited to those with intermediate differentiation. The clinical significance of these alterations requires further study.